Role of zinc trafficking in male fertility: from germ to sperm - Foresta, Carlo; Garolla, Andrea; Cosci, Ilaria; Menegazzo, Massimo; Ferigo, Marco; Gandin, Valentina; De Toni, Luca (Human reproduction (Oxford), 2014)
STUDY QUESTION What are the dynamics of zinc (Zn) trafficking in sperm, at the testicular, epididymal and ejaculate levels? SUMMARY ANSWER Zn transporters are peculiarly expressed in the cells of the germ line and Zn uptake is maximal at the post-epididymal phase, where Zn is involved in the regulation of sperm functions. WHAT IS KNOWN ALREADY Zn is known to influence several phases of sperm life, from germ cell development to spermiation. Zn trafficking across the membrane is allowed by specific families of transporters known as the ZnTs, which are involved in effluent release, and the Zips, which mediate uptake. STUDY DESIGN, SIZE, DURATION We enrolled 10 normozoospermic healthy participants in an infertility survey programme, as well as 5 patients affected by testicular germ cell cancer, and 18 patients presenting with obstructive azoospermia, without mutations of the CFTR gene, and undergoing assisted reproductive technologies. PARTICIPANTS/MATERIALS, SETTING, METHODS The research study was performed at our University Clinic. Semen samples, or biopsies or fine needle aspirates from the testis or epididymis, were obtained from each of the participants. Protein expression of main members of the ZnT and Zip families of Zn transporters was examined in human testis and epididymis samples by immunofluorescence. Quantification of sperm Zn content was performed by flow cytometry, atomic absorption spectrometry (AA) and autometallography. MAIN RESULTS AND THE ROLE OF CHANCE Intratubular cells of the germ line displayed a high redundancy of Zip family members involved in Zn uptake, while ZnT transporters were more represented in epididymis. Testicular and epididymal spermatozoa contained less Zn than ejaculated spermatozoa (2.56 ± 0.51 and 12.58 ± 3.16 versus 40.48 ± 12.71 ng Zn/106cells, respectively). Gain of hypermotility and acrosomal reaction were significantly linked to the loss of Zn content in ejaculated spermatozoa. LIMITATIONS, REASONS FOR CAUTION This was an ancillary study performed on a small cohort of normozoospermic subjects. Although these results clarify the Zn trafficking during different phases of sperm life, no conclusive information can be drawn about the fertilizing potential of sperm, and the overall pregnancy outcomes, after Zn supplementation. WIDER IMPLICATIONS OF THE FINDINGS Our data disclose the dynamics of Zn trafficking during over the sperm lifespan. STUDY FUNDING/COMPETING INTEREST(S) No external funding was sought or obtained for this study. No conflict of interest is declared.